Systematic Literature Review: E-Module Development with PBL Approach to Enhance Students' Critical Thinking and Creativity in Science Education - Adisan Adisan; Agus Ramadan; Abdul Syukur; Aris Doyan (Gema Cendekia Institute, 2025)
Critical thinking skills are one of the core competencies in 21st-century education, especially in science learning that emphasizes analysis, evaluation, and problem solving. This study aims to identify trends and research focuses on critical thinking in the context of science education through a bibliometric approach. Data were collected from the Dimensions database using the keywords